2014
DOI: 10.1007/978-1-4939-0709-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Biomedical Literature in the Current Information Landscape

Abstract: i. Summary Biomedical and life sciences literature is unique because of its exponentially increasing volume and interdisciplinary nature. Biomedical literature access is essential for several types of users including biomedical researchers, clinicians, database curators, and bibliometricians. In the past few decades, several online search tools and literature archives, generic as well as biomedicine-specific, have been developed. We present this chapter in the light of three consecutive steps of literature acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Although health sciences may be broader than medicine, in general, it is reasonable to think that the greater part of the health sciences collection is represented by medicine‐related subjects. Khare, Leaman, and Lu () report that biomedical publications continue to grow rapidly, with over one million published each year. In addition, a number of studies (Jejeebhoy, ; Marušić, ; Momen, ) explain the influence of medical and social sciences research on the progress of the society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although health sciences may be broader than medicine, in general, it is reasonable to think that the greater part of the health sciences collection is represented by medicine‐related subjects. Khare, Leaman, and Lu () report that biomedical publications continue to grow rapidly, with over one million published each year. In addition, a number of studies (Jejeebhoy, ; Marušić, ; Momen, ) explain the influence of medical and social sciences research on the progress of the society.…”
Section: Introductionmentioning
confidence: 99%
“…Although health sciences may be broader than medicine, in general, it is reasonable to think that the greater part of the health sciences collection is represented by medicine-related subjects. Khare, Leaman, and Lu (2014) report that biomedical publications continue to grow rapidly, with over one million published each…”
Section: Introductionmentioning
confidence: 99%
“…The biomedical literature is estimated to make up a large portion of these published studies [2] and the introduction of internet has opened up the possibility to share and exchange information across research groups to a point that was unthinkable even in the recent past [3]. The web has opened the possibility of easier ways to exchange ideas through social media [4][5][6][7][8] and crowd science [9,10], to retrieve information via open access publications [11], to easily search for information, thanks to databases and repositories [12][13][14][15]. Digital publications have also abated publishing costs, triggering an increase of editorial initiatives, i.e., publications, especially in the natural sciences [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Google Scholar is now the first point of call for scholars and that habits developed searching there are translated across to other databases (Marks and Le 2016). Other challenges noted in research is that searching is complex and the selection of keywords and retrieving results is daunting (Khare, Leaman, and Lu 2014). There are great differences in the content and services of databases (Lefebvre et al 2013) and researchers are hampered by inappropriate search strategies, time constraints, and contradictory information (Ho et al 2016).…”
Section: Introductionmentioning
confidence: 99%